2018
DOI: 10.1186/s12940-018-0394-x
|View full text |Cite
|
Sign up to set email alerts
|

The Ramazzini Institute 13-week pilot study on glyphosate and Roundup administered at human-equivalent dose to Sprague Dawley rats: effects on the microbiome

Abstract: BackgroundGlyphosate-based herbicides (GBHs) are broad-spectrum herbicides that act on the shikimate pathway in bacteria, fungi, and plants. The possible effects of GBHs on human health are the subject of an intense public debate for both its potential carcinogenic and non-carcinogenic effects, including its effects on microbiome. The present pilot study examines whether exposure to GBHs at doses of glyphosate considered to be “safe” (the US Acceptable Daily Intake - ADI - of 1.75 mg/kg bw/day), starting from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
94
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 77 publications
1
94
1
1
Order By: Relevance
“…Although the precise role of each of these bacteria phyla for brain physiology is, to our knowledge, far from understood, a few studies have suggested that a dysregulation of Bacteroidetes or Firmicutes populations is associated with mental health disorders, including autism and Alzheimer's disease . To support our findings, other studies conducted not only in rats, but also in bees, report similar changes in Bacteroidetes and/or Firmicutes following Glyphosate or Glyphosate‐based herbicide exposure . Similarly, the population of the genera Alloprevotella is increased in the present study, whereas other studies have found an association between Parkinson and Alzheimer's disease and a reduced population of the family of Prevotellaceae .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Although the precise role of each of these bacteria phyla for brain physiology is, to our knowledge, far from understood, a few studies have suggested that a dysregulation of Bacteroidetes or Firmicutes populations is associated with mental health disorders, including autism and Alzheimer's disease . To support our findings, other studies conducted not only in rats, but also in bees, report similar changes in Bacteroidetes and/or Firmicutes following Glyphosate or Glyphosate‐based herbicide exposure . Similarly, the population of the genera Alloprevotella is increased in the present study, whereas other studies have found an association between Parkinson and Alzheimer's disease and a reduced population of the family of Prevotellaceae .…”
Section: Discussionsupporting
confidence: 85%
“…132,133 To support our findings, other studies conducted not only in rats, but also in bees, report similar changes in Bacteroidetes and/ or Firmicutes following Glyphosate or Glyphosate-based herbicide exposure. 40,48,127,128 Similarly, the population of the genera Alloprevotella is increased in the present study, whereas other studies have found an association between Parkinson and Alzheimer's disease and a reduced population of the family of Prevotellaceae. [134][135][136][137] It is obviously important to note that these studies are only correlational and the precise consequences of the 69 revealed that low (5 mg kg -1 ), medium (50 mg kg -1 ) or high doses (500 mg kg -1 ) of Glyphosate altered levels of Zn 2+ and Fe 2+ in the liver, spleen and kidney in a dose dependent-way in adult male rat.…”
Section: Molecular Target Of Glyphosatecontrasting
confidence: 57%
See 1 more Smart Citation
“…A recent study showed that glyphosate affects honey bees by altering their microbial community composition, and this may be a threat to bee health due to a greater susceptibility to pathogens . For the mammalian microbiome, Lozano et al found a gender‐specific effect on the composition of intestinal microbiota in rats and Mao et al revealed effects in rats on the bacterial composition in the F1 generation …”
Section: Introductionmentioning
confidence: 99%
“…9 For the mammalian microbiome, Lozano et al found a gender-specific effect on the composition of intestinal microbiota in rats 10 and Mao et al revealed effects in rats on the bacterial composition in the F1 generation. 11 Apart from the inhibitory effect of glyphosate on EPSPS, some microorganisms are able to metabolize glyphosate. The first biodegradation route relies on the cleavage of the C&bond;P bond by carbon-phosphorus lyase, resulting in sarcosine and inorganic phosphorus.…”
mentioning
confidence: 99%